Stigma against patients with HIV/AIDS in the rapid expansion of antiretroviral treatment in large drug injection-driven HIV epidemics of Vietnam - Phung Quoc Tat Than; Bach Xuan Tran; Cuong Tat Nguyen; Nu Thi Truong; Thao Phuong Thi Thai; Carl A. Latkin; Cyrus S. H. Ho; Roger C. M. Ho (BMC, 2019)
Abstract Background Despite existing efforts to provide antiretroviral treatment (ART) for all HIV-diagnosed people, stigma deprives them of the highest attainable health status and challenges the effectiveness of ART program in Vietnam. This study aimed to assess five dimensions of HIV-related stigma and explore its associated factors among ART patients in a multisite survey. Implications of this study support the development of HIV policies to improve patients' access, utilization, and outcomes of ART program toward the 90-90-90 goal in Vietnam. Methods A total of 1133 ART patients who were recruited by convenience sampling method from 8 ART clinics in Hanoi and Nam Dinh in a cross-sectional study from January to August 2013. Multivariate logistic regression was employed to identify factors associated with stigmatization. Results The majority of participants reported experiencing stigmatization due to shame (36.9%), blame/judge (21.6%), and discrimination (23.4%). Further, 91.5% of participants disclosed their HIV status with others. The likelihood of experiencing stigmatization did not only associate with the patients' socioeconomic status (e.g., age, occupation, education) and HIV status disclosure, but also their health problems. Those with anxiety or depression and perceived lower quality of life were more likely to experience stigma. Conclusions To maximize the efficiency of the ART program, it is essential to develop interventions that reduce stigma involving individuals, families, and communities, and recognize and address complex health problems especially those patients showing depressive symptoms. Increasing quality of life of HIV-positive patients by providing vocational training, financial, family, and peer support will reduce the likelihood of experiencing stigma.